1999
DOI: 10.1046/j.1440-1681.1999.02995.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Sympathetic Nervous System Regulation

Abstract: 1. Females are protected against the development of hypertension. The purpose of the current review is to present the evidence for gender differences in the regulation of the sympatho-adrenal nervous system and to determine if these differences support the hypothesis that, in females, the regulation of the sympathetic nervous system (SNS) is altered such that sympatho-adrenal activation is attenuated or sympatho-adrenal inhibition is augmented. 2. The central control of sympatho-adrenal function is different i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
141
1
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(160 citation statements)
references
References 47 publications
13
141
1
5
Order By: Relevance
“…In fact, there is growing evidence that sex affects the regulation of the sympathetic nervous system. It has been shown that pathways regulating the sympathetic nervous system appear to be more sensitive to excitatory stimuli and less sensitive to inhibitory stimuli in men than in women (12). This means that a similar level of external stimuli would more easily and/or more markedly induce excitation of the sympathetic nervous system in men than in women, and would seem to offer a good explanation of the present results.…”
Section: Discussionsupporting
confidence: 62%
“…In fact, there is growing evidence that sex affects the regulation of the sympathetic nervous system. It has been shown that pathways regulating the sympathetic nervous system appear to be more sensitive to excitatory stimuli and less sensitive to inhibitory stimuli in men than in women (12). This means that a similar level of external stimuli would more easily and/or more markedly induce excitation of the sympathetic nervous system in men than in women, and would seem to offer a good explanation of the present results.…”
Section: Discussionsupporting
confidence: 62%
“…48 In that report, the baroreceptor reflex sensitivity controlling MSNA was found to be increased in relation to increased plasma levels of oestrogen and progesterone. 48 Although we did not examine the mechanisms underlying the observed gender-related differences, taking the above considerations together with previously published reports, 20,41,49,50 it is reasonable to raise the possibility that the lower sympathetic activity in women could be related to their greater sympatho-inhibitory baroreceptor reflexes than those in men. This normal genderrelated difference would then affect the level of the central sympathetic hyperactivity attained in women and men with hypertension.…”
Section: For Hypertensive Women (F-eht) and Men (M-eht) Normotensivementioning
confidence: 94%
“…Apart from the severity of hypertension and lipid disorders, other possible factors related to cardiovascular risk in postmenopausal women have included vascular responsiveness to neural and neurotransmitter effects, as well as the levels of various hormonal systems. 2,5,28,31 Such considerations assume relevance when considering the choice of hypertension management and antihypertensive therapy.…”
Section: Groupmentioning
confidence: 99%